A study protocol of the rehabilitative efficacy of cardiovascular ultrasound therapy after percutaneous coronary intervention in patients with coronary artery disease: A multicenter, parallel-group, randomized controlled study - Chunwei He; Jie Peng; Hong Liu; Lin Zhong; Yanjin Wei; Hao Qiu; Chuanliang Liu; Nana Lv; Lixia Liu; Xuewen Qi; Fenglei Zhang; Beian You; et al. (PLoS ONE, 2025)
Background Coronary artery disease (CAD) is a leading cause of mortality and disability, placing heavy burdens on healthcare systems. Although cardiovascular ultrasound therapy has demonstrated effectiveness and safety in improving refractory angina, relevant clinical studies are rare and clinical evidence is lacking. Methods and design This is a prospective, parallel-group, randomized controlled trial. We enrolled 200 patients with coronary artery disease who had undergone percutaneous coronary intervention (PCI) and randomized them into two groups. The intervention group will be given usual-practice plus cardiovascular ultrasound therapy intervention and the control group will be given only usual-practice intervention. After 20 treatments with cardiovascular ultrasound therapy, high‐sensitivity C‐reactive protein in serum will be used as the primary outcome measures. The following will be used in determining secondary outcomes: indicators of serum myocardial injury, blood lipid levels, markers of endothelial function, inflammatory factors, hemodynamic indicators, echocardiography, ultrasound examination for carotid plaques, 6-minute walk test, short-term variability in heart rate, and mental health assessment. The researchers plan to test the outcome indicators at multiple time points. Statistical analyses will be performed using SPSS version 26 statistical software (IBM, Armonk, NY). Discussion This is the first clinical study of the rehabilitative efficacy of cardiovascular ultrasound therapy in the treatment of CAD after PCI. Clinical recovery currently depends mainly on modalities such as medication, exercise, and nutritional therapy; therefore, cardiovascular ultrasound therapy, as a new mode of therapy, might become a major advance in the treatment of CAD after PCI. Trial registration ClinicalTrials.gov NCT06640400